2012
DOI: 10.29333/ejgm/82552
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Depression among Incarcerated Woman in Central Prison, Peshawar, Pakistan

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 10 publications
1
16
2
1
Order By: Relevance
“…The current study also demonstrated that prisoners who had children experienced depression more than those who did not have children. A study conducted among women incarcerated in the Peshawar Central Prison, Pakistan had reported similar findings [ 11 ]. As reported by Munoz-Laboy et al and Campos et al, lack of close relationship with children might be the reason for high occurrence of depression among inmates [ 19 , 22 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The current study also demonstrated that prisoners who had children experienced depression more than those who did not have children. A study conducted among women incarcerated in the Peshawar Central Prison, Pakistan had reported similar findings [ 11 ]. As reported by Munoz-Laboy et al and Campos et al, lack of close relationship with children might be the reason for high occurrence of depression among inmates [ 19 , 22 ].…”
Section: Discussionmentioning
confidence: 54%
“…This figure is massively higher than the national estimate of depression in the general population in Ethiopia which is 5% [14]; this prevalence is also higher than findings of a population-based study conducted in southwest of the country (15%) [22]. Higher prevalence of depression in prison population compared to the general population had been consistently reported from studies done in Nigeria [9, 19],, Brazil [20], Pakistan [11] and Iran [9–11] with some variations in magnitude among the studies. Such variations in the prevalence of depression among the studies might be due to differences in the tools, cut off value used to measure it, variations in prison environments, sample size, and variations in the overall characteristics of the study settings that could be related to the prevalence of depression in one way or another.…”
Section: Discussionmentioning
confidence: 78%
“…However, It is higher than results of study in Iran among sentenced prisoners (29%) [18], reports of Bureau of Justice Statistics among State prisoners (23%) and jail inmates (30%) [22], systematic review of 62 studies from 12 countries; which reported 10% among men and 12% among females [20], study conducted in Agaro town (15%) [39], in low- to middle-income countries which ranges from 5.9 to 11.1% [28], and northern Uganda (29.2%) [40]. On the other hand it is lower than results reported on Woman in Central Prison, Peshawar, Pakistan (59.4%) [17], by studies done in Germany among general adults [41]. The possible explanation for the differences might be socio-demographic, socio-economic and cultural difference between our study population and the listed studies.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature review done in 24 countries revealed rates of depression of around 10 and 14% in males and females prisoners respectively [15]. Many studies reported different levels of depression among detainees; 46.1% among Norwegian inmates [16], 59.4% among incarcerated women in Central Prison of Peshawar, Pakistan [17], 29% among sentenced prisoners in Iran [18], 18% among prisoners of England and Wales (including anxiety) [19], 10 and 12% among men and women prisoners respectively [20], 23.3% among prisoners of Durban, South Africa (including psychotic and anxiety disorders) [21], and 49% among prisons and jails according to special reports of U.S. department of Justice [22]. In Kaliti Federal Prisons, Addis Ababa, Ethiopia, 61.9% of prisoners were found to have high levels of mental distress in general [23].…”
Section: Introductionmentioning
confidence: 99%
“…As far as the Pakistani situation is concerned, no study highlighted the situation of prison libraries. However, literature (Ali and Shah, 2011; Khan et al , 2012; Shagufta et al , 2015) identified poor facilities in Jails and inmates specifically, young and women prisoners depressed due to ignorance of their legal rights. These studies also mentioned that the feelings of suffocation and isolation caused suicidal attacks in Jails.…”
Section: Review Of Literaturementioning
confidence: 99%